Mineralization Study of Volcanic Rocks in Colo Volcano Tojo Una-Una Central Celebes - Asrafil Asrafil; Teguh Hilmansyah; Muslimin U Botjing; Eka Yuliastri (Universitas Muslim Indonesia, 2020)
Colo Volcano is an active volcano located on Una-Una Island, Tojo Una-Una Regency, Central Sulawesi Province. Volcanism and magmatism of Mount Colo are still in progress, and this has certainly triggered mineralization in volcanic rocks which is interesting for study. This research aims to reveal the mineralization characteristics of volcanic rocks in the study area. This research was conducted through investigative methods in the form of field observations and laboratory through petrographic and rock chemistry (X-Ray Defraction analysis) to reveal the presence of alteration minerals as a characteristic of mineralization. The results of this study indicate that the volcanic rocks present are tuff and volcanic breccia in the form of pyroclastic deposits associated with alluvial material and andesite rocks. Identification of alteration minerals through XRD test shows the presence of hydrothermal alteration minerals with a formed temperature of 300 ° C such as Quartz, Calcite, Clinochlore, Albite, Dickite, Andesine, and K-Feldspar which are classified into Argillic and Propylitic alteration types.